The Impact of Flexible Working Arrangements on Work-Life Balance for Generation Z Employees - Khosyatillah, Prita Balena; Anggraeni, Dewi Soerna (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study aims to examine the relationship between flexible working arrangements and work-life balance among Generation Z employees in Indonesia. Using a quantitative approach with Pearson product-moment correlation analysis, this study involved 110 respondents aged 15–30 years who were employed in non-shift-based work. Data were collected using validated Likert-scale questionnaires that measure flexible working (based on Hyland's three dimensions: available flexibility, preference for flexibility, and use of flexibility) and work-life balance (based on four dimensions: WIPL, PLIW, WEPL, and PLEW). The results of the Pearson correlation test showed a significant positive relationship between flexible working arrangements and work-life balance (r = 0.349, p < 0.05). This indicates that the higher the perceived flexibility at work, the better the individual's ability to balance work and personal life. These findings are in line with Clark's Work-Family Border Theory and emphasize the importance of flexible policies in promoting employee well-being, especially among Generation Z workers.